1999
DOI: 10.1039/a901331h
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of partially overlapping tailing peaks in diode array high performance liquid chromatography using purity ratios

Abstract: A new approach to deconvolution of diode array HPLC data is described. It is illustrated by the chromatograms of 2-and 3-hydroxypyridine undertaken at pH 4.8, 5.1 and 5.2 representing three different qualities of resolution from almost totally overlapping to well resolved. In all cases peaks are tailing, typical of many real situations. The first step is to select wavelengths using the normalised spectra at each point in time. Next a purity curve is obtained from these wavelengths, which is related to a real p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…14,17 It has been shown that this condition together with other knowledge and constraints on the system is sufficient to provide good deconvolution. 18 This is compatible with theoretical predictions by Manne in 1995. 19 An analyst often has considerable knowledge of a system.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…14,17 It has been shown that this condition together with other knowledge and constraints on the system is sufficient to provide good deconvolution. 18 This is compatible with theoretical predictions by Manne in 1995. 19 An analyst often has considerable knowledge of a system.…”
Section: Introductionsupporting
confidence: 91%
“…Purity curve calculations have been described in greater detail previously; 18 however, the implementation used in this paper involves additional steps for wavelength selection and a final overall scaling.…”
Section: Purity Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of enantiomers giving partially overlapping peaks was also made possible by using different chemometric treatments of chromatographic ultraviolet signals, e.g., quantification of pseudoephedrine enantiomers [4]. Deconvolution of partially overlapping tailing peaks in photodiode array HPLC using purity ratios has also been applied [5]. Semi-automatic deconvolution of chromatographic data to give pure spectral and chromatographic profiles has been found beneficial in the quantitative determination of some pharmaceutical mixtures [6].…”
Section: Introductionmentioning
confidence: 99%